2022
DOI: 10.3390/fishes7050241
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Intestinal Microbial Composition between Red Claw Crayfish (Cherax quadricarinatus) and Red Swamp Crayfish (Procambarus clarkii) Cultured in Pond

Abstract: Intestinal microbiota communities participate in several metabolic processes in the host, and are highly correlated to digestion, nutrition, growth, and immunity. However, the intestinal microbiota of aquatic invertebrates is poorly understood, especially in freshwater crayfish. In this study, the intestinal microbiota of two important freshwater economic aquaculture species, the invasive species, the red swamp crayfish (Procambarus clarkii, Pc), and the introduced species, the red claw crayfish (Cherax quadri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Stage-specific, sex-specific, and species-specific microbiota compositions in growth responses have been reported in vertebrates and invertebrates, such as Cetobacterium in the giant salamander (Andrias davidianus) [36], Rhodobacterales in threespine stickleback (Gasterosteus aculeatus) [37] and Vibrio coralliilyticus in the red claw crayfish (Cherax quadricarinatus) [30]. Candidatus Hepatoplasma was detected only in the two-and three-month-old prawn groups.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Stage-specific, sex-specific, and species-specific microbiota compositions in growth responses have been reported in vertebrates and invertebrates, such as Cetobacterium in the giant salamander (Andrias davidianus) [36], Rhodobacterales in threespine stickleback (Gasterosteus aculeatus) [37] and Vibrio coralliilyticus in the red claw crayfish (Cherax quadricarinatus) [30]. Candidatus Hepatoplasma was detected only in the two-and three-month-old prawn groups.…”
Section: Discussionmentioning
confidence: 96%
“…Diversity differences in the intestinal microbiota have been reported in a number of shrimp species, such as Indian white shrimp (Penaeus indicus), Pacific white shrimp (Litopenaeus vannamei), red claw crayfish (Cherax quadricarinatus) and red swamp crayfish (Procambarus clarkii) [28][29][30]. The intestinal microbiota of Indian white shrimp differed among different stages and showed decreasing diversity with age.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a study [106] in which the administration of seaweeds (Ulva lactuca) as a feed additive promoted the growth of Enterobacteriaceae in specimens of white shrimp (Penaeus vannamei). These microorganisms resulted to be of crucial importance for the correct development and functioning of intestinal microflora, being involved in a series of processes, including digestion and food absorption, production of advantageous metabolites, and protection against pathogens [107,108]. Lately, it has been reported that the microencapsulation of Enterobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…This result was associated with changes in the biochemical immune response of the crayfish PO. Since previous studies have shown that gut microbiome differs between male and female of P. clarkii , affecting their immune responses ( Chen et al, 2022 ), we suggest including females in future studies to examine the toxic effects of MP on crustaceans, by assessing histological and physiological changes as well as hemolymph microbiome reactions in the presence of MP. Studying other markers of crayfish immune system such as cellular responses (e.g., hemocyte parameters), receptors and signaling molecules ( Bouallegui, 2021 ) would be useful to fully understand the relationship between the animal’s physiological response and microbiota changes.…”
Section: Discussionmentioning
confidence: 99%